Business Feasibility Study Of Electronic Government System Application Development Project Using Capital Budgeting Method By PT Sangkuriang Internasional - William Rusly Widadi; Mentiana Sibarani (UNIVED Press, 2025)
Capital budgeting is an important part of a project, because it is a process for business evaluation that is useful for assessing the feasibility of a project. In previous projects, PT Sangkuriang Internasional did not calculate capital budgeting of the project and only looked at the possible profits based on the predicted cash flow. Capital budgeting will be used as a reference for companies or organizations to continue or not a project. The purpose of this study is to analyze the feasibility of the Electronic-Based Government System Application Development project from an economic perspective for the Sangkuriang Internasional company. This research method uses a quantitative descriptive method. Data will be taken from ongoing projects and some will be forecasted to complete incomplete data. The forecasting carried out will follow the advice given by the company's finance department. The results of the feasibility analysis show that the Electronic-Based Government System application development project is feasible to work on. From the results of the economic feasibility analysis, the value obtained was NPV = Rp 920.868.596,90, PI = 2,20, IRR = 26,497% per month (317,968% in 1 project), PP = 5.76 months, and RoI = 14.09% with the Weighted Average Cost of Capital used is 10%. So based on the results of economic feasibility shows that the Electronic-Based Government System application development project is still feasible to be continued by the company PT Sangkuriang Internasional.